Effects of Flipped Learning Utilizing Digital Literacy on Critical Thinking and Self-directed Learning in Nursing Students in Korea: A Quasi-experimental Study. - Lee, Minjae; Kang, Insoon; Park, Seung-Bin (Journal of Korean Academy of Fundamentals of Nursing, 2025)
Purpose: The aim of this study was to investigate the impact of flipped learning digital literacy on critical thinking and self-directed learning in nursing students in Korea. Methods: A quasi-experimental study with a non-equivalent control group pre-test-post-test design was employed to examine the effects of flipped learning using digital literacy on critical thinking and self-directed learning in nursing students. The participants were third-year nursing students at B University in Korea. Flipped learning was administered to 36 students in the experimental group for 13 weeks, while traditional lecture-based instruction was provided to 35 students in the control group from September to December 2023. Data were analyzed using SPSS Statistics 27.0. The independent t-test was conducted to compare effects between the experimental and control groups. Results: The post-test scores for critical thinking showed differed between the experimental and control groups, however, it was not statistically significantly (t=-0.86, p=.391). However, the scores for self-directed learning showed a significant difference in favor of the experimental group (t=2.06, p=.042). Conclusion: Flipped learning using digital literacy effectively enhances self-directed learning. However, critical thinking requires long-term follow-up to ensure that significant changes persist. This finding suggests that both short- and long-term effects should be considered when evaluating educational outcomes.